The rise and fall of a vancomycin-resistant clone of Enterococcus faecium among broilers in Sweden. (June 2019) - Nilsson, Oskar; Alm, Erik; Greko, Christina; Bengtsson, Björn
Highlights: There has been a significant decrease in the VRE-occurrence among Swedish broilers. There has been no change in the dominating clone of VRE among Swedish broilers. The factor(s) behind the decrease (or the previous increase) remain unknown. Abstract: Objectives: Historically, vancomycin-resistant enterococci (VRE) have been very common among farm animals in Europe, and they can still be readily isolated using media supplemented with vancomycin. An increase in the occurrence of VRE among broilers in Sweden was reported during 2000–2005. This was due to the spread of one clone of VRE in the apparent absence of selective pressure. The aims of this study were to estimate the current occurrence of VRE among Swedish broilers and to investigate if there had been any changes with regards to the dominating clone and antimicrobial resistance pattern. Methods: Caecal samples (n = 100) collected at slaughter from healthy broilers were cultured on Slanetz-Bartley agar supplemented with vancomycin (16 mg/L). Presumptive VRE were identified to species using MALDI-TOF MS, susceptibility tested using broth micro-dilution, and whole genome sequenced to investigate the genetic relationship with previous isolates. Results: Eleven (11%) of the samples were positive for VRE. This was a statistically significant decrease in the proportion of positive samples from 2010. The same clone as before still prevailed. Conclusions: The occurrence of VRE among broilers in Sweden has decreased. However, just as the occurrence of VRE among Swedish broilers increased in the apparent absence of selective pressure, the reasons for the decrease is unknown.